2009
DOI: 10.1016/j.yebeh.2009.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Threshold-independent functional MRI determination of language dominance: A validation study against clinical gold standards

Abstract: Functional MRI (fMRI) is often used for presurgical language lateralization. The most common approach calculates a laterality index (LI) based on suprathreshold voxels. However, strong dependencies between LI and threshold can diminish the effectiveness of this technique; in this study we investigated an original methodology that is independent of threshold. We compared this threshold-independent method against the common threshold-dependent method in 14 epilepsy patients who underwent Wada testing. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 54 publications
2
59
0
1
Order By: Relevance
“…The effect of threshold selection is consistent with reports in the literature that choice of thresholds is not straight-forward and needs to be carefully considered [33,38]. We found that at increasingly stringent thresholds, the percent overlap between MEG and fMRI decreased substantially.…”
Section: Discussionsupporting
confidence: 89%
“…The effect of threshold selection is consistent with reports in the literature that choice of thresholds is not straight-forward and needs to be carefully considered [33,38]. We found that at increasingly stringent thresholds, the percent overlap between MEG and fMRI decreased substantially.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, it has been demonstrated that the combination of multiple tasks, a language-specific region of interest approach and implementation of statistical threshold-independent approaches for determination of hemispheric lateralization, provides more reliable lateralization that correlates better with the criterion standard Wada test. 20,21 One limitation of this study includes the exclusion of the cerebellum from region-of-interest analysis. The cerebellum has demonstrated fMRI activation during silent articulation.…”
mentioning
confidence: 99%
“…Therefore, it is recommended that multiple language tasks be administered in fMRI in order to calculate language dominance as a continuous variable. [13] In localising language function, several tasks have been shown to reliably activate expressive and receptive language cortex (Table 1). Generally, verbal fluency paradigms require expressive language and secondarily, language comprehension and therefore activations are noted in Broca's areas and Wernicke's area in the dominant hemisphere, in addition to pre-motor cortex, posterior fusiform gyrus, middle temporal gyrus and dorsolateral prefrontal cortex.…”
mentioning
confidence: 99%